Maximizing the Benefits of Public-Private Partnership for Infrastructure in Energy Sector: A Study of Key Challenges and Recommendations - STEELYANA , Evy; AULIA, Raynaldi P. (Journal of Governance, Taxation and Auditing, 2024)
This study aimed to analyze the main themes of research in Public-Private Partnership (PPP) in energy infrastructure development using a systematic literature review. The data was taken from highly selected international journals, and the study found that 48% of the publications were from Q1 Scopus Indexed journals. The most popular topics in the research were PPP challenges, project management and regulatory implications, risk management, and PPP financing. This study significantly contributes to the field by highlighting the main research themes in PPP in energy infrastructure development. It provides insights into the topics currently being researched and emphasizes the implementation of PPP in the energy sector. The study's findings can serve as a valuable reference for researchers, policymakers, and practitioners interested in PPP in energy infrastructure development and its relationship to accounting and finance. Additionally, the study provides a roadmap for future research in this area, highlighting areas that require further exploration and investigation.